The Effect of Variations in the Addition of Vitamin C Doses in Urine on Glucose Levels with the Benedict Method - Achmadi Achmadi; Aina Chumairoh; Septiani Septiani (Jurnal Ilmiah Kesehatan (JIKA), 2022)
Urine glucose or glucosuria detected by Benedict's method is a pathological condition found to be falsely positive in healthy individuals while consumption of vitamin C during the pandemic can also interfere with urinalysis results. This study aimed to determine the effect of variations in the dose of vitamin C added to urine samples on glucose levels. Pre-experimental research was conducted on 15 healthy student urine samples using a purposive sampling technique. Urine glucose levels were checked using Benedict's method for further intervention with 250 mg, 500 mg, and 1000 mg of vitamin C added to the urine of 25 ml each. Data were analyzed by the Kruskal Wallis test and the Mann Whitney follow-up test it was significant if p < 0,05. The results of the urine glucose examination were found to be positive in Benedict's method with the addition of a dose of vitamin C. Kruskal Wallis analysis showed that the variation in the dose of vitamin C had an effect on Benedict's method with a p-value of 0,000 and the Mann Whitney test showed that the three doses of vitamin C were different in each Urine glucose results on Benedict's method.